Priorização de atividades de remediação no município de São Paulo através de técnica de tomada de decisão multicriterial - Zampieri, Maria Rita [UNESP]; Cerri, Leandro Eugênio da Silva [UNESP] (My University, 2015)
Currently, due to the increase of environmental problematic and the urbanization of areas, previously used for industrial purpose, the risks associated to the health of the population have increased considerably. The limitations and capabilities of this environment is an efficient mechanism of environmental analysis, because the strategies for sustainable development are based on accurate assessment of the carrying capacity of the territory and its recovery front of human activity. Therefore, this study aims to present a proposal for prioritizing areas that need remediation activities in São Paulo, using technique of decision-making. Through the gathering of information on the natural environment and man-made, including the definition of scale and area, natural compartmentalization, zoning and population density, applied the multicriteria method of analysis AHP (Analytic Hierarchy Process) in four levels, considering criteria, sub-criteria and alternatives. The results showed a survey of contaminated areas and areas suspected of contamination and the product resulting from the application of the AHP methodology, that obtained as a result the priority of remediation on industries areas. In conclusion, that the industrial areas, which is now being disabled by numerous complex real estate, are those that present the biggest risk to the population, therefore priority in the decision regarding the need for remediation.
Prioritization of remediation activities in São Paulo municipality through multicriteria decision-making techniques